PENGARUH KECERDASAN EMOSIONAL DAN PERILAKU BELAJAR PADA TINGKAT PEMAHAMAN AKUNTANSI PADA MAHASISWA AKUNTANSI FEB UWKS - Agustin, Tyssa Amelia Vega; Wany, Eva; Prayitno, Budi (STIE Mahardhika, 2024)
The contemporary work environment underscores the necessity of competition among individuals to enhance skills and expertise in specific fields. Therefore, this study aims to investigate the improvement in skills and expertise, particularly in the context of students' comprehension of accounting. The research focuses on accounting students in the Faculty of Economics and Business at Wijaya Kusuma University Surabaya (UWKS). Employing an associative and quantitative approach, the study utilizes an online questionnaire as the primary instrument for data collection from respondents. The research population includes 51 students, with a sample size of 51 individuals, and 36 respondents provided responses. Classical assumption tests, such as normality, multicollinearity, and heteroskedasticity tests, were applied, along with multiple linear regression for quantitative data analysis. Hypothesis testing involved partial t-tests, simultaneous F-tests, and coefficient of determination assessments. The analysis revealed that emotional intelligence and learning behavior variables each had a positive partial effect. Simultaneously, both significantly influenced students' comprehension levels, as evidenced by a significant F-value (33.338) and a Sig. value lower than 0.05. Thus, both partially and simultaneously, this research demonstrates that emotional intelligence and student learning behavior significantly impact the comprehension levels of students at the Faculty of Economics and Business (FEB) at UWKS.